Lifestyle behaviour change for preventing the progression of chronic kidney disease: a systematic review - Karine Manera; Allison Tong; Jonathan Craig; Nicole Evangelidis; Adrian Bauman; Valeria Saglimbene (BMJ Open)
Objectives Modifying lifestyle can prevent the progression of chronic kidney disease (CKD) but the specific elements which lead to favourable behaviour change are not well understood. We aimed to identify and evaluate behaviour change techniques and functions in lifestyle interventions for preventing the progression of CKD.Design Systematic review.Data sources MEDLINE, EMBASE, CINAHL and PsycINFO.Eligibility criteria Trials of lifestyle behaviour change interventions (including diet, physical activity, smoking and/or alcohol) published to September 2018 in adults with CKD stages 1–5.Data extraction and synthesis Trial characteristics including population, sample size, study setting, intervention, comparator, outcomes and study duration, were extracted. Study quality was independently assessed by two reviewers using the Cochrane risk of bias tool. The Behaviour Change Technique Taxonomy v1 was used to identify behaviour change techniques (eg, goal setting) and the Health Behaviour Change Wheel was used to identify intervention functions (eg, education). Both were independently assessed by three reviewers.Results In total, 26 studies involving 4263 participants were included. Risk of bias was high or unclear in most studies. Interventions involved diet (11), physical activity (8) or general lifestyle (7). Education was the most frequently used function (21 interventions), followed by enablement (18), training (12), persuasion (4), environmental restructuring (4), modelling (2) and incentivisation (2). The most common behaviour change techniques were behavioural instruction (23 interventions), social support (16), behavioural demonstration (13), feedback on behaviour (12) and behavioural practice/rehearsal (12). Eighteen studies (69%) showed a significant improvement in at least one primary outcome, all of which included education, persuasion, modelling and incentivisation.Conclusion Lifestyle behaviour change interventions for CKD patients frequently used education, goal setting, feedback, monitoring and social support. The most promising interventions included education and used a variety of intervention functions (persuasion, modelling and incentivisation).PROSPERO registration number CRD42019106053.